Human rights incorporated? Business and human rights in an age of neoliberalism - Kelsall, Michelle Ruby (2019)
How can we understand the turn toward ‘business and human rights’ at the start of the new millennium? Why did this field of academic inquiry, policy development and legal practice emerge in the aftermath of the global financial crisis in 2008? And how might the field of business and human rights change the ways in which international lawyers theorize and practice international human rights law in the twenty-first century? These are the three central research questions that this thesis asks and seeks to answer. In so doing it provides a descriptive analytical critique of the emergence of ‘business and human rights’. Drawing on a close reading of United Nations archival records from the past forty years, the thesis explains the arrival of the field of ‘business and human rights’ through ongoing failed attempts by the Third World and its allies to regulate the conduct of transnational corporations. It situates its emergence in a series of struggles between state representatives, civil servants, business and civil society to reimagine the international economic order anew. The thesis then explores why those attempts fell short, what this might tell us about the primary modus operandi of the field as it is emerging today, and how it might still be imagined differently. This thesis argues that the concept of ‘embedded pragmatism’ can help explain both the emergence of the field of business and human rights and its central methods and dynamics. ‘Embedded pragmatism’ refers to a mode of legal reasoning utilized by different actors to regulate the conduct of transnational corporations in the societies in which they operate. The descriptive move of embedded pragmatism collapses the distinction between legal (mandatory/state-regulating) and non-legal (voluntary/self-regulating) obligations. The normative move claims that this is of benefit to those most vulnerable to human rights abuse. By excavating the recent past and interrogating the basis upon which business and human rights has emerged, the thesis questions whether this collapse in distinction really is of benefit to the poor, the disenfranchised and the marginalized, or whether it instead gives rise to a technocratic form of human rights managerialism, and if so, what might be done about it. The thesis is written at a time when increasing anxieties about our era of unrivalled capitalism have manifested within international legal scholarship. This has included scholars questioning the ontogenesis of international investment law since at least the 1970s and its relationship to the ongoing immiseration of many in the Third World (including the Third World which has manifested in the First). These anxieties are accompanied by a growing body of scholarship in human rights historiography assessing the relationship between the rise of human rights and the ascendance of neoliberalism since the 1970s. Although both bodies of scholarship touch peripherally on business and human rights, neither has considered its emergence as a significant area of research inquiry. This thesis provides a timely intervention and corrective, first by giving an account of the emergence of the field and then by diagnosing why it operates as it does and positioning it within this wider frame. It argues that embedded pragmatism creates a dynamic in which managerialism is prioritized, but that the field can still be imagined differently.